The secret what great leaders know and do - Blanchard, Kenneth H. (BK business book, 2009)
In the now classic business fable, The Secret, Debbie, a struggling leader finds herself about to lose her job due to poor performance. In a desperate attempt to save her career, she enrolls in a new mentoring program offered by her company. Much to her surprise, Debbie finds her mentor is the president of the company (Jeff Brown). Debbie decides that all she needs is the answer to one question, 'What is the secret of great leaders?' Over the next 18 months Jeff explains to Debbie that the secret is rooted in an attitude. He tells her that she must be willing to become a serving leader rather than a self- serving leader. The secret is that all great leaders Serve. The story unfolds as Debbie learns and applies each of these imperatives with her team. As a result, Debbie's team goes from worst to first. They become the highest performing team within the company. In the end, Debbie understood that all the changes and improvements were the result of the choices she made as a leader. She realized that to Serve is a choice.